2014
DOI: 10.1038/srep04335
|View full text |Cite
|
Sign up to set email alerts
|

An extended steepness model for leg-size determination based on Dachsous/Fat trans-dimer system

Abstract: What determines organ size has been a long-standing biological question. Lawrence et al. (2008) proposed the steepness hypothesis suggesting that the protocadherin Dachsous/Fat (Ds/Ft) system may provide some measure of dimension to the cells in relation to the gradient. In this paper we extended the model as a means of interpreting experimental results in cricket leg regeneration. We assumed that (1) Ds/Ft trans-heterodimers or trans-homodimers are redistributed during cell division, and (2) growth would ceas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The golgi-localized protein kinase Fj regulates the activity of Ft and Ds by phosphorylation (Pan, 2010;Brittle et al, 2010;Bando et al, 2009Bando et al, , 2011, and these proteins have been shown to be necessary for the establishment of planar cell polarity (PCP) during imaginal disc growth (Matis and Axelrod, 2013). Planar cell polarity is established by the unequal distribution of Ft and Ds protein heterodimers within the cell (Lawrence et al, 2008;Yoshida et al, 2014).…”
Section: The Fat/hippo Signaling Pathwaymentioning
confidence: 99%
“…The golgi-localized protein kinase Fj regulates the activity of Ft and Ds by phosphorylation (Pan, 2010;Brittle et al, 2010;Bando et al, 2009Bando et al, , 2011, and these proteins have been shown to be necessary for the establishment of planar cell polarity (PCP) during imaginal disc growth (Matis and Axelrod, 2013). Planar cell polarity is established by the unequal distribution of Ft and Ds protein heterodimers within the cell (Lawrence et al, 2008;Yoshida et al, 2014).…”
Section: The Fat/hippo Signaling Pathwaymentioning
confidence: 99%
“…For the molecular mechanisms of the leg regeneration, the Dachsous/Fat steepness model has been proposed, in which the gradient of Fat and Dachsous signals maintains the positional information in the PD axis and determines leg size (Bando et al, 2009). This model was theoretically verified (Yoshida et al, 2014). Although functions of Dachsous/Fat orthologs in vertebrate regeneration are unknown, it is very interesting that Dachsous/Fat orthologs or similar molecules determine differences in cell adhesiveness along the PD axis of urodeles, and regulate the normalization of segmental structures during limb regeneration working as positional information.…”
Section: Discussionmentioning
confidence: 98%
“…To verify the steepness hypothesis, Yoshida and others proposed a mathematical model (Fig. 9) (Yoshida et al, 2014). They assumed that (1) Ds/ Ft trans-heterodimers or trans-homodimers are redistributed during cell division, and (2) growth would cease when a differential of the dimer across each cell decreases to a certain threshold (Yoshida et al, 2014).…”
Section: Theoretical Verification Of the Ds/ft Steepness Modelmentioning
confidence: 99%